Fast and spatially heterogeneous cooling rates at amphibolite-facies conditions in the Lepontine Alps (Switzerland) - Tagliaferri, Alessia; Moulas, Evangelos; Schmalholz, Stefan M.; Schenker, Filippo Luca (Geochemistry, geophysics, geosystems, 2025)
The Lepontine dome (European Central Alps) is constituted by basement nappes under Alpine regional Barrovian metamorphism, yet the duration and pattern of its post-peak amphibolite-facies cooling remain uncertain. We examine garnet-rim compositional re-adjustment and employ inverse multicomponent diffusion modeling to estimate apparent cooling rates. We selected six garnet paragneisses at different tectonic levels within the Lepontine nappe pile. Garnet crystal rims are syn-kinematic with respect to the amphibolite-facies metamorphic foliation and display coupled Mn increase and Mg decrease, indicative of retrograde reactions. Using geothermobarometry, we estimate re-equilibration post-peak temperatures between 577 and 661°C at pressures between 0.5 and 1.3 GPa. Our inferred cooling rates reveal a spatial trend: the shear zone below the main nappe (Maggia-Adula) records rapid cooling with rates between 100 and 400°C/Myr, the footwall cools slower with a rate of 2°C/Myr, and the migmatitic belt in the southern Lepontine dome shows intermediate cooling rates between 20 and 50°C/Myr. We perform one-dimensional (1D) thermal and two-dimensional (2D) thermo-kinematic models. The observed cooling rate distribution, characterized by high rates along the shear zone and significantly lower rates in the footwall, matches the predictions of 2D models where a hotter nappe is emplaced onto a colder one. Both 1D and 2D models suggest that high cooling rates above 600°C and above 0.5 GPa observed along the main shear zone are likely not caused solely by heat advection and diffusion associated with nappe stacking and exhumation. Local heat sources, such as the percolation of hot fluids or shear heating, may have contributed to high cooling rates.